TRIM37 Mediates Chemoresistance and Maintenance of Stemness in Pancreatic Cancer Cells via Ubiquitination of PTEN and Activation of the AKT–GSK-3β–β-Catenin Signaling Pathway - Chen, Shiyu; He, Zhiwei; Zhu, Changhao; Liu, Yanqing; Li, Lin; Deng, Lu; Wang, Jun; Yu, Chao; Sun, Chengyi (Frontiers in Oncology, 2020)
Abstract Purpose: The tripartite motif-containing family member TRIM37 is involved in a number of important biological and pathological processes, and it has recently been shown to be an essential regulator of protein ubiquitination and a contributor to tumorigenesis. We previously showed that TRIM37 is overexpressed in and promotes the proliferation and invasion of pancreatic cancer (PC). Methods: Sphere formation, flow cytometric, qRT-PCR, western blot, colony formation, EdU incorporation, mouse xenograft model, TUNEL and IHC assays were performed to detect the role of TRIM37 in stemness and chemoresistance of PC in vitro and in vivo. Bioinformatics analysis and dual-luciferase reporter assays were used to determine which intracellular pathways might mediate the effects of TRIM37 in PC cells. Immunofluorescent(IF) staining, co-immunoprecipitation(CO-IP), protein stability and ubiquitination assays were performed to investigate the relationship between TRIM37 and PTEN. Results: TRIM37 modulates the ubiquitination and degradation of the tumor suppressor phosphatase and tensin homolog (PTEN), which negatively regulates the AKT–GSK-3β–β-catenin signaling pathway, thereby sustaining aberrant activation of PC cells. High expression of TRIM37 combined with low expression of PTEN correlates with poor survival of PC patients. Conclusions: Collectively, our results suggest that inhibition of the TRIM37–AKT–GSK-3β–β-catenin axis may be a promising strategy for treatment of PC.